Burlington Zephyr at a Century of Progress Exposition, 1934
On May 26, 1934, the ZEPHYR broke all long-distance, non-stop World's Records for railroad trains when it ran 1015 miles from Denver, Colo. To Chicago in 785 minutes to signalize the reopening of A Century of Progress Exposition. The ZEPHYR left Denver 5:04 AM Mountain Time and reached Halstead Street, Chicago 7:09 PM Central Time - 13 hr. 5 min. Its average speed on the spectacular dawn-to-dusk flight was 77.6 miles an hour... its top speed 112.5 miles an hour.